PENDIDIKAN BERBASIS MULTIKULTURAL DI MTsN 1 PESISIR SELATAN SUMATERA BARAT (ANALISIS PEMBELAJARAN FIKIH) - Fithidayati Fithidayati (LP2M IAI NURUL HAKIM, 2022)
Education with a multicultural basis has urgency in responding to the diversity of existing understandings. As a result of the various schools of thought and khilafiyah debates, Muslims are often divided. Therefore, students should learn the importance of having an understanding of this issue. This research uses qualitative research procedures with information analysis methods including data reduction, data presentation, and drawing conclusions. The results of the study indicate that the curriculum and teaching resources are dimensions of multicultural values ​​in fiqh learning. Incorporating multicultural values ​​in the comparison of schools of law in fiqh learning, especially promoting the ideals of tolerance and non-fanaticism, inclusivity and non-discrimination, teaching the origin of differences, teaching ethical principles to resolve differences, and promoting ideals peace and unity. Having a sensitive and responsive attitude to culture, being skilled at minimizing conflict, and knowing other people's languages ​​and cultures are some of the implications of multicultural values ​​in fiqh learning. As well as learning that includes the capacity to deny stereotypes and distortions of ethnic groups.